2019
DOI: 10.1111/ens.12344
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of the orchid Cephalanthera spp. by Parallelomma vittatum (Meigen, 1826) (Diptera: Scathophagidae) in Japan

Abstract: It is important to understand the interactions between orchids and their herbivores, especially considering the rarity of most orchids and the potential negative effects of pests on orchid reproduction. Here, we report the infestation of leaves of Cephalanthera spp. orchids by Parallelomma vittatum (Scathophagidae) in Japan. The present study represents the first report of P. vittatum on orchid hosts in Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Notably, J. tokunagai is currently damaging orchid fruits throughout Japan, and it has been a significant orchid pest since 1923. Recently, damage has been sufficiently severe and widespread across orchid genera (e.g., Ogura‐Tsujita et al, 2019; Ogura‐Tsujita et al, 2021) that some authors have suggested that the species may be alien to Japan (Onuki, 2007; Suetsugu et al, 2019). However, our results indicate that this species has been part of the ecosystem in Japan for at least 100 years and should not be considered recently introduced exotic species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, J. tokunagai is currently damaging orchid fruits throughout Japan, and it has been a significant orchid pest since 1923. Recently, damage has been sufficiently severe and widespread across orchid genera (e.g., Ogura‐Tsujita et al, 2019; Ogura‐Tsujita et al, 2021) that some authors have suggested that the species may be alien to Japan (Onuki, 2007; Suetsugu et al, 2019). However, our results indicate that this species has been part of the ecosystem in Japan for at least 100 years and should not be considered recently introduced exotic species.…”
Section: Discussionmentioning
confidence: 99%
“…Fly damage to Japanese orchids, many of which are already endangered or otherwise threatened, is dramatically increasing, thus hindering sexual production and undermining conservation efforts (Ogura‐Tsujita et al, 2019; Suetsugu et al, 2018a). Onuki (2007) and Suetsugu et al (2019) suggested that J. tokunagai in Japan may have an exotic origin, but no data are available to suggest historical regional or temporal damage estimates.…”
Section: Introductionmentioning
confidence: 99%